Primary central nervous system sarcoma with DICER1 mutation-treatment results of a novel molecular entity in pediatric Peruvian patients - Diaz Coronado, RY (2021)
Background: A high frequency of primary central nervous system (CNS) sarcomas was observed in Peru. This article describes the clinical characteristics, biological characteristics, and outcome of 70 pediatric patients. Methods: Data from 70 pediatric patients with primary CNS sarcomas diagnosed between January 2005 and June 2018 were analyzed. DNA methylation profiling from 28 tumors and gene panel sequencing from 27 tumors were available. Results: The median age of the patients was 6 years (range, 2-17.5 years), and 66 of 70 patients had supratentorial tumors. DNA methylation profiling classified 28 of 28 tumors as primary CNS sarcoma, DICER1 mutant. DICER1 mutations were found in 26 of 27 cases, TP53 mutations were found in 22 of 27 cases, and RAS-pathway gene mutations (NF1, KRAS, and NRAS) were found in 19 of 27 tumors, all of which were somatic (germline control available in 19 cases). The estimated incidence in Peru was 0.19 cases per 100,000 children (<18 years old) per year, which is significantly higher than the estimated incidence in Germany (0.007 cases per 100,000 children [<18 years] per year; P < .001). Patients with nonmetastatic disease (n = 46) that were treated with a combination therapy had a 2-year progression-free survival (PFS) rate of 58% (95% CI, 44%-76%) and a 2-year overall survival rate of 71% (95% CI, 57%-87%). PFS was the highest in patients treated with chemotherapy with ifosfamide, carboplatin, and etoposide (ICE) after upfront surgery followed by radiotherapy and ICE (2-year PFS, 79% [59%-100%], n = 18). Conclusions: Primary CNS sarcoma with DICER1 mutation has an aggressive clinical course. A combination of surgery, chemotherapy, and radiotherapy seems beneficial. An underlying cancer predisposition syndrome explaining the increased incidence in Peruvian patients has not been identified so far.